HOXA10 Regulates Expression of Cytokeratin 15 in Endometrial Epithelial Cytoskeletal Remodeling. (July 2014) - Kallen, Amanda N.; Haines, Kaitlin; Taylor, Hugh S.
Objective: The mammalian cytoskeleton is composed in part from keratin filaments which form a complex, highly dynamic intracellular network. We investigate the expression of cytokeratin 15 (CK15) in human endometrium and its regulation by HOXA10 in the human endometrial cell lines. Methods: Endometrial biopsies from throughout the menstrual cycle (N = 32) were evaluated for CK15 protein expression by immunohistochemistry using a mouse monoclonal antibody. The human endometrial epithelial cell line (Ishikawa) was transfected with pcDNA/HOXA10. Total RNA was isolated and quantitative real-time polymerase chain reaction was performed to determine expression levels of CK15. Results: In the peri-implantation window (days 16 through 23) CK15 protein expression in glandular epithelium of human endometrium decreased to 50% of proliferative phase expression levels. Expression of CK15 messenger RNA decreased by 99% ( P < .05) after pcDNA/HOXA10 transfection of Ishikawa cells. The CK15 expression corresponded to the time of maximal secretory epithelial remodeling. Conclusion: Gene expression of CK15 is decreased in a HOXA10-dependent fashion in human endometrial epithelial cells. Expression decreases in the peri-implantation period concurrent with maximal HOXA10 expression. Dramatic changes in cellular architecture are necessary to achieve the secretory changes in the endometrial epithelium that bring about the implantation window. Alterations in CK15 likely facilitate these cytoskeletal changes, ultimately promoting endometrial receptivity.